Strain partitioning along the anatectic front in the Variscan Montagne Noire massif (southern French Massif Central). Issue 8 (24th August 2015) - Rabin, Mickael; Trap, Pierre; Carry, Nicolas; Fréville, Kevin; Cenki‐Tok, Bénédicte; Lobjoie, Cyril; Goncalves, Philippe; Marquer, Didier
Abstract: We decipher late‐orogenic crustal flow characterized by feedback relations between partial melting and deformation in the Variscan Montagne Noire gneiss dome. The dome shape and finite strain pattern of the Montagne Noire Axial Zone (MNAZ) result from the superimposition of three deformations (D1, D2 and D3). The early flat‐lying S1 foliation is folded by D2 upright ENE‐WSW folds and transposed in the central and southern part of the MNAZ into steep D2 high‐strain zones consistent with D2 NW‐SE horizontal shortening, in bulk contractional coaxial deformation regime that progressively evolved to noncoaxial dextral transpression. The D2 event occurred under metamorphic conditions that culminated at 0.65 ± 0.05 GPa and 720 ± 20°C. Along the anatectic front S1 and S2 foliations are transposed into a flat‐lying S3 foliation with top‐to‐NE and top‐to‐SW shearing in the NE and SW dome terminations, respectively. These structures define a D3 transition zone related to vertical shortening during coaxial thinning with a preferential NE‐SW to E‐W directed stretching. Depending on structural level, the metamorphic conditions associated with D3 deformation range from partial melting conditions in the dome core to subsolidus conditions above the D3 transition zone. We suggest that D2 and D3 deformation events were active at the same time and resulted from strain partitioning on both sides of the anatectic front that may correspond to a major rheological boundary within the crust. Key Points: Three deformation events formed the Montagne Noire Axial Zone strain pattern Partial melting of the gneissic core occurred at 0.65 GPa and 720°C Strong strain partitioning occurs along the anatectic front